Simulation model for road cycling time trials with a non-constant drag area - Rømcke, E.; Sorensen, E.; Aas, P.; Bardal, L.; Harneshaug, S.; Lian, M.; Oggiano, L.; Drawer, S. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
In a time trial in road cycling, the choice of equipment has a great impact on the results. The purpose of this paper is to expand an existing model for road cycling to account for changes in drag coefficient with changes in the Reynolds number of the air flow. The model gives a prediction of the performance of a cyclist given a certain equipment setup. The model may be used to test different setups and identify the fastest one for a given race. Simulations with existing models have given a mean absolute error of 3.87% of the total time. Validation of the model in this paper yielded predictions that had a mean absolute error of 3.22%. The model correctly predicts the fastest setup, but further testing and validation is required to show its statistical accuracy. Potential improvements of the model includes improved data sets to increase precision of the inputs, and thereby reduce simplifications and assumptions.